2020
DOI: 10.3390/jcm9113612
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Hemoglobin to Serum Creatinine Ratio with In-Hospital Adverse Outcomes after Percutaneous Coronary Intervention among Non-Dialysis Patients: Insights from a Japanese Nationwide Registry (J-PCI Registry)

Abstract: Although baseline hemoglobin and renal function are both important predictors of adverse outcomes after percutaneous coronary intervention (PCI), scarce data exist regarding the combined impact of these factors on outcomes. We sought to investigate the impact and threshold value of the hemoglobin to creatinine (Hgb/Cr) ratio, on in-hospital adverse outcomes among non-dialysis patients in a Japanese nationwide registry. We analyzed 157,978 non-dialysis patients who underwent PCI in 884 Japanese medical institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Moreover, activation of sympathetic nerves and the renin-angiotensin-aldosterone system, chronic inflammation oxidative stress, and endothelial dysfunction may also be associated with high levels of creatinine. 23 Multivariate logistic regression analysis showed that serum creatinine and UA are not independent risk factors for ISR in PCHD. These findings may be attributable to the patients we selected, and we will include more patients in the future to improve our research.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, activation of sympathetic nerves and the renin-angiotensin-aldosterone system, chronic inflammation oxidative stress, and endothelial dysfunction may also be associated with high levels of creatinine. 23 Multivariate logistic regression analysis showed that serum creatinine and UA are not independent risk factors for ISR in PCHD. These findings may be attributable to the patients we selected, and we will include more patients in the future to improve our research.…”
Section: Discussionmentioning
confidence: 97%
“…We extracted patient‐based data from the prospectively ongoing J‐PCI registry for the present study. The overview of this Japanese nationwide PCI registry has been previously published in detail 15–17 . Briefly, the J‐PCI registry is a prospective, multicenter, nationwide database of the Japanese Association of Cardiovascular Intervention and Therapeutics (CVIT) and is designed to record patients' characteristics, procedural data, and clinical outcomes after PCI.…”
Section: Methodsmentioning
confidence: 99%
“… 21 22 Furthermore, Numasawa et al reported that the combined haemoglobin and renal function index was correlated with the short-term prognosis of patients undergoing percutaneous coronary intervention. 6 Therefore, we speculate that renal function combined with anaemia would be a strong prognostic factor in patients undergoing TAVI.…”
Section: Discussionmentioning
confidence: 91%
“… 4 5 A combined anaemia and renal failure index have been reported to be associated with adverse outcomes following percutaneous coronary intervention. 6 This study aimed to determine the predictive accuracy of a combined anaemia and renal failure index for predicting the 1-year prognosis of patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%